Quantifying the impact of underlying measurement error on cervical spinal cord diffusion tensor imaging at 3T. Issue 6 (18th May 2016) - By, Samantha; Smith, Alex K.; Dethrage, Lindsey M.; Lyttle, Bailey D.; Landman, Bennett A.; Creasy, Jeffrey L.; Pawate, Siddharama; Smith, Seth A.
Abstract : Purpose: To empirically characterize and quantify the impact of gradient weighting schemes on the appearance and fidelity of diffusion tensor imaging of the human spinal cord in vivo in clinically relevant scan time equivalents (STE). Materials and Methods: In five healthy controls at 3T, we evaluated test–retest reproducibility and performed voxelwise analysis of diffusion tensor imaging (DTI)‐derived indices (fractional anisotropy [FA], mean [MD], axial [AD], and radial [RD] diffusivity) in the cervical spinal cord to assess spatial dependencies of measurement error and differences across three different sampling schemes (6, 15, and 32 directions) at STE of 4.5, 9, and 18 minutes. A subjective assessment was also performed. Results: With six directions, column‐specific errors are highest (effect size = 2.9%, 4.4%, 7.2% for FA in dorsal column, lateral column, and gray matter) and different than the 15‐direction scheme ( P < 0.05). STE sequences with 15 and 32 directions exhibited small differences in error ( P > 0.05). For FA and AD, measurement errors are prevalent in gray matter, while partial volume effects with cerebrospinal fluid heavily influence RD. Measurement errors decreased with increasing scan time ( P < 0.01), albeit with diminishing returns at scan times longer than 9 minutes ( P < 0.05). Conclusion: A 15‐direction scheme of 9 minutes yields measurements of the cervical spinal cord with low error. J. Magn. Reson. Imaging 2016;44:1608–1618.